2001
DOI: 10.1142/s0218271801000780
|View full text |Cite
|
Sign up to set email alerts
|

Black Holes of a Minimal Size in String Gravity

Abstract: A lower limit for a neutral black hole size is obtained in the frames of the string gravity model with the second order curvature correction. It is shown that this effect remains when the third order curvature correction is also taken into account and argued that such restriction does exist in all perturbative orders of curvature expansions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…without having an unambigous and complete theory of quantum gravity [10]. Furthermore, some cosmologically relevant wavelengths must, at some early stage, have been trans-Planckian [13,14,15,16]; this can cast doubts on the validity of the cosmological perturbation predictions of inflation. Finally, the usual and simpler models of inflation need a scalar field [17], whose theoretical properties demanded for setting up the inflationary phase are not obviously compatible with those obtained from well-motivated fundamental particle physics theory [18,19] (a new perspective was, however, suggested [20]).…”
Section: Introductionmentioning
confidence: 99%
“…without having an unambigous and complete theory of quantum gravity [10]. Furthermore, some cosmologically relevant wavelengths must, at some early stage, have been trans-Planckian [13,14,15,16]; this can cast doubts on the validity of the cosmological perturbation predictions of inflation. Finally, the usual and simpler models of inflation need a scalar field [17], whose theoretical properties demanded for setting up the inflationary phase are not obviously compatible with those obtained from well-motivated fundamental particle physics theory [18,19] (a new perspective was, however, suggested [20]).…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that pbhs are a great probe of the early universe with a varying gravitational constant (Carr 2001). Finally, significant progress has been made in the understanding Send offprint requests to: A. Barrau, e-mail: barrau@isn.in2p3.fr of the evaporation mechanism itself, both at usual energies (Parikh & Wilczek 2000) and in the near-planckian tail of the spectrum (Barrau & Alexeyev 2001;Alexeyev et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that s are a useful probe of the early Universe with a varying gravitational constant (Carr 2000). Finally, significant progress has been made in the understanding of the evaporation mechanism itself, both at usual energies (Parikh & Wilczek 2000) and in the near-Planckian tail of the spectrum (Barrau & Alexeyev 2001;Alexeyev et al 2001;Alexeyev et al 2002).…”
Section: Introductionmentioning
confidence: 99%